2005
DOI: 10.1177/107110070502601002
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Ankle Osteochondral Allograft Transplantation for Tibiotalar Joint Arthritis

Abstract: Fresh osteochondral transplantation for tibiotalar joint arthritis is a promising alternative to arthrodesis and prosthetic replacement. Early results demonstrate successful outcomes and good pain relief in over half the patients in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 42 publications
4
71
0
6
Order By: Relevance
“…Our patient achieved an outstanding outcome as regards pain and mobility, with 94 points on the AOFAS scale for the left ankle and 92 for the right, although short-term results are similar to those of other authors. 18,20,21 Some authors believe ankle transplantation to be the primary treatment in osteochondral lesions of the astragalus and as an intervention to gain some time in salvage situations for post-traumatic osteoarthritides, secondary to arthritis, to osteonecrosis, or to haemophilic joint disease in young patients. Jeng et al 22 suggest that transplant candidates should be patients who are too young for a replacement arthroplasty, with a low body mass index, and normal limb alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient achieved an outstanding outcome as regards pain and mobility, with 94 points on the AOFAS scale for the left ankle and 92 for the right, although short-term results are similar to those of other authors. 18,20,21 Some authors believe ankle transplantation to be the primary treatment in osteochondral lesions of the astragalus and as an intervention to gain some time in salvage situations for post-traumatic osteoarthritides, secondary to arthritis, to osteonecrosis, or to haemophilic joint disease in young patients. Jeng et al 22 suggest that transplant candidates should be patients who are too young for a replacement arthroplasty, with a low body mass index, and normal limb alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 5 (45.5%) patients with failure, 3 of them had repeat allografting with success, 1 was revised to total ankle arthroplasty while the other has had no further surgery. They concluded that poor results occurred in ankles with mismatch of size and graft thickness (<7mm) [61].…”
Section: Allograft Ankle Arthroplastymentioning
confidence: 99%
“…It involves replacing all or part of the arthritic ankle joint with a cadaveric OC allograft. This is a technically demanding procedure that requires an anatomically matching allograft in terms of side and size to host bone [59][60][61][62][63]. It is usually indicated for young active patients that are not suitable for total ankle arthroplasty.…”
Section: Allograft Ankle Arthroplastymentioning
confidence: 99%
“…Meehan et al reported in their case series that all, but one patient (10/11) was found to have human leukocyte antigen cytotoxic antibodies following transplantation. 2 Furthermore, the one patient without antibodies was a renal transplant patient on immunosuppressive medications, and notably had an excellent result. It has been argued that while the articular cartilage portion of an allograft is immune-privileged, the underlying bone is not and contains cells that can elicit an immune response.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The operation involves replacing injured, diseased or missing regions of bone and articular cartilage with matched specimens from a cadaveric donor. The goal is to restore a congruent articular surface with viable hyaline cartilage, and osteochondral allograft has several advantages over the alternative surgical treatments for both conditions.…”
Section: Introductionmentioning
confidence: 99%